Wireless transmission of voltage transients from a chronically implanted neural stimulation device. (1st April 2022) - Frederick, Rebecca A; Troyk, Philip R; Cogan, Stuart F
Abstract: Objective. Consistent transmission of data from wireless neural devices is critical for monitoring the condition and performance of stimulation electrodes. To date, no wireless neural interface has demonstrated the ability to monitor the integrity of chronically implanted electrodes through wireless data transmission. Approach. In this work, we present a method for wirelessly recording the voltage transient (VT) response to constant-current, cathodic-first asymmetric pulsing from a microelectrode array. We implanted six wireless devices in rat sciatic nerve and wirelessly recorded VT measurements throughout a 38 week implantation period. Main results. Electrode maximum cathodic potential excursion (Emc ), access voltage, and driving voltage (extracted from each VT) remained stable throughout the 38 week study period. Average Emc (from an applied +0.6 V interpulse bias) in response to 4.7 µ A, 200.2 µ s pulses was 267 ± 107 mV at week 1 post-implantation and 282 ± 52 mV at week 38 post-implantation. Access voltage for the same 4.7 µ A pulsing amplitude was 239 ± 65 mV at week 1 post-implantation and 268 ± 139 mV at week 38 post-implantation. Significance. The VT response recorded via reverse telemetry from the wireless microelectrode array did not significantly change over a 38 week implantation period and was similar to previously reported VTs from wired microelectrodes with the same geometry. Additionally, the VT response recorded wirelessly in phosphate buffered saline before and after device implantation appeared as expected, showing significantly less electrode polarization and smaller access voltage than the VT response in vivo .